The Anticipated Hazards Due to Errors In Using Laser In Medicine & Recommendationms for the Safe Use Of Medical Laser Systems in Iraqi Hospitaals - Farrohaa, Azzaam S.; Hajim, Khaleel I. (Journal of the Faculty of Medicine Baghdad, 2007)
• Causes of Laser HazardI - Inherent Hazards to Laser Beam Direct or reflected laser beams have consequential health effects range from minor skin burn to irreversible eye injuries. The hazards depend on thepower output and wavelength of the used laser and depend on the exposure time and MPE. ti & 2)